The Role of Local Government in Raising Awareness of Land and Building Taxpayers in Mamuju Regency - Astika Astika; Herlina Sakawati; Aris Baharuddin (Jurnal Aktor, 2022)
This study aims to determine the role of the government in increasing the awareness of land and building taxpayers in Mamuju Regency and to determine the factors that influence the awareness of land and building taxpayers in Mamuju Regency. This type of research is descriptive qualitative with data collection techniques, namely observation, interviews and documentation. The results of this study indicate that the government's role in increasing awareness of land and building taxpayers in Mamuju Regency is carried out well, but extension activities have not been evenly distributed. Indicators of improving services have not been implemented well in the Bapenda Mamuju Regency such as the lack of response from employees and the lack of infrastructure facilities provided. The Bapenda in Mamuju Regency has not given awards to taxpayers at all.